Memtein: The fundamental unit of membrane-protein structure and function. (January 2019) - Overduin, Michael; Esmaili, Mansoore
Highlights: Memtein is coined to describe a membrane protein bound to a layer of biologically relevant, structured lipids. Devolopment of styrene maleic acid lipid particle (SMALP) technology to prepare native nanodiscs reviewed. Impact of SMALP and related methods on structural biology and memtein research is explored. Abstract: The concept of a memtein as the minimal unit of membrane function is proposed here, and refers to the complex of a membrane protein together with a continuous layer of biological lipid molecules. The elucidation of the atomic resolution structures and specific interactions within memteins remains technically challenging. Nonetheless, we argue that these entities are critical endpoints for the postgenomic era, being essential units of cellular function that mediate signal transduction and trafficking. Their biological mechanisms and molecular compositions can be resolved using native nanodiscs formed by poly(styrene-co-maleic acid) (SMA) copolymers. These amphipathic polymers rapidly and spontaneously fragment membranes into water-soluble discs holding a section of bilayer. This allows structures of complexes found in vivo to be prepared without resorting to synthetic detergents or artificial lipids. The ex situ structures of memteins can be resolved by methods including cryo-electron microscopy (cEM), X-ray crystallography (XRC), NMR spectroscopy and mass spectrometry (MS). Progress in the field demonstrates that memteins are better representations of how biology actually works in membranes than naked proteins devoid of lipid, spurring on further advances in polymer chemistry to resolve their details.